2004
DOI: 10.1128/jcm.42.4.1570-1576.2004
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Characterization of the Spike Protein of the Severe Acute Respiratory Syndrome Coronavirus

Abstract: Severe acute respiratory syndrome (SARS) is a novel infectious disease caused by the SARS-associated coronavirus (SARS-CoV). There are four major structural proteins in the SARS-CoV, including the nucleocapsid, spike, membrane, and small envelope proteins. In this study, two sets of truncated fragments of spike protein were generated, the first were approximately 210-bp nonoverlapping fragments and the second were overlapping segments of 750 to 900 bp. From these 23 fragments, we identified a fragment of 259 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 24 publications
2
64
0
Order By: Relevance
“…This is consistent with the reports by Lu et al (28) and Wang et al (29), in which they demonstrated that the fragments of aa 441-700 and 599 -620, which overlap with sequence of site IV, also reacted with most SARS sera tested. We further showed that several peptides derived from site IV were strongly reactive with the antisera from mice and rabbits immunized with inactivated SARS-CoV (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the reports by Lu et al (28) and Wang et al (29), in which they demonstrated that the fragments of aa 441-700 and 599 -620, which overlap with sequence of site IV, also reacted with most SARS sera tested. We further showed that several peptides derived from site IV were strongly reactive with the antisera from mice and rabbits immunized with inactivated SARS-CoV (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…Because insertion of foreign genes into genomes of nonsegmented negative strand viruses such as NDV can confer attenuation that increases with insert size (34), we also made a separate NDV-BC-vectored vaccine construct expressing the N-terminal 762-aa S1 domain (NDV-BC/S1). The S1 domain has been reported to contain the receptor-binding site of S as well as major neutralizing epitopes (35). The various vaccine viruses were readily recovered and amplified, achieving peak titers of Ϸ10 7.5 to 10 8.0 pfu/ml in DF-1 cells and 10 8.5 to 10 9.0 in embryonated chicken eggs (data not shown).…”
Section: Resultsmentioning
confidence: 78%
“…Among the structural proteins, including M, E, and N, only the S protein elicits neutralizing antibody (138). The major immunodominant epitope in S protein lies between amino acids 441 and 700 (139).…”
Section: Humoral Immune Response To Sars-cov Infectionmentioning
confidence: 99%